Frequency and characterization of pluripathological patients going to an urban ambulatory in Lara – Venezuela (Revista Venezolana de Salud Pública, 2021)
In Venezuela there is no official data on pluripathological patients (PP), however an increase in patients with multiple chronic diseases is observed in clinical practice, which may meet the criteria for pluripathology, this led to the need to determine the frequency and characteristics of PP who attended the urban type II ambulatory “Dr. Ramón E. Gualdrón”. A cross-sectional descriptive study was performed, with an accidental non-probabilistic sample of 165 patients, over 20 years of age, of both sexes. A file consisting of: identification data and diagnostic criteria of PP was applied through the interview technique. The SPSS statistical package was used. It was obtained that 24.24% were PP. Of the women who attended, 25.44% had pluripathology, as did 21.57% of the men. Of the older adults 35.62% were PP and of the intermediate 17.28%. According to the number of clinical categories, 75% presented two, 22.50% three and 2.50% four; the most frequent were F (75%), A (42,50%) and H (40%), the predominant combinations F + H, A + F and E + F. It is the first Venezuelan study on pluripathology. The frequency of PP was found to be almost 25% higher than estimated in Spain; it predominates in older adults with a mean age lower than that reported in that country, it is also present in people between 41-65 years of age. It affects both sexes similarly and it represents a highly fragile population, which cardiovascular and metabolic diseases predominate, being these in themselves a public health problem, so pluripathology also could be it.
Keywords: Pluripathology; chronic disease; frailty; multimorbidity